2014
DOI: 10.1111/lam.12315
|View full text |Cite
|
Sign up to set email alerts
|

Patulin reduction in apple juice by inactivated Alicyclobacillus spp.

Abstract: Inactivated Alicyclobacillus cells can efficiently reduce patulin concentration in apple juice. It provides a theoretical foundation for recycling of Alicyclobacillus cells from spoiled apple juice to reduce the source of pollution and the cost of juice industry. This is the first report on the use of Alicyclobacillus to remove patulin from apple juice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…This is one last detail on a possible benefit and positive role of Alicyclobacillus spp. These microorganisms are generally labeled as spoilers or super-spoilers for acidic drinks; however, Yuan et al [ 43 ] heat-inactivated alicyclobacilli cells and used them as adsorbing tools to remove/reduce patulin in apple juice. The removal rate was ca .…”
Section: Characteristic Of Alicyclobacillus Sppmentioning
confidence: 99%
“…This is one last detail on a possible benefit and positive role of Alicyclobacillus spp. These microorganisms are generally labeled as spoilers or super-spoilers for acidic drinks; however, Yuan et al [ 43 ] heat-inactivated alicyclobacilli cells and used them as adsorbing tools to remove/reduce patulin in apple juice. The removal rate was ca .…”
Section: Characteristic Of Alicyclobacillus Sppmentioning
confidence: 99%
“…These results are in good agreement with previous reports that the PAT adsorption capability of the HI microorganism was strain-dependent. The differences in the PAT adsorption abilities of the HI cells and spores of Alicyclobacillus strains are due to their distinct cell wall compositions and different organizations within the cell structures [ 12 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hatab et al [ 14 ] identified two strains with high detoxifying capacities, namely the LR5 and EF10, which removed 80.4% and 64.5% of PAT from apple juice, respectively. The inactivated microbial cells of LAB and yeasts have previously been reported to reduce PAT from apple juice and aqueous solutions [ 12 , 13 , 17 , 21 ]. The adsorption of PAT by the HI cells and spores of all of the tested strains have not shown any negative impact on the quality of the apple juice based on the measurements of various quality parameters except for the HI cells and spores of Alicyclobacillus cycloheptanicus DSM 4006 (A06) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations